Causality Relationship between Advertising Expenditure and Sales: A Study of Indian Service Sector. (August 2014) - Sharma, Sneha; Kapur, Deepak
Advertising plays a major role in marketing for the companies. The conventional approach suggests that advertising by the company helps in increasing the sales. This article investigates the relationship between advertising expenditure and sales with reference to Indian service sector. It is analyzing the long-run and short-run properties of the sales–advertising expenditure relationship for 106 companies. Data from year 2000 to 2012 have been used. Augmented Dickey–Fuller test (ADF), Engle–Granger two-step cointegration, Granger causality test and the vector error correction model (VECM) have been used to test the relationship. The results of the five groups based on the size of the companies showed varied results. The companies in the first and second quintiles were analyzed using error correction models since the variables were found to be cointegrated. For the companies in the third, fourth and fifth quintile, the variables were not cointegrated, and these were analyzed using VAR. The causality between sales and advertising expenditure was tested using Granger causality test. The results show that the relationship between advertising expenditure and sales varied with the size of the company. The larger companies showed a bidirectional relationship between advertising and sales, whereas in smaller companies a long-run increase in sales led to a decrease in advertising expenditure.